First Isolation and Molecular Characterization of blaCTX-M-121-Producing Escherichia coli O157:H7 From Cattle in Xinjiang, China - Su, Zhanqiang; Tong, Panpan; Zhang, Ling; Zhang, Mengmeng; Wang, Dong; Ma, Kaiqi; Zhang, Yi; Liu, Yingyu; Xia, Lining; Xie, Jinxin (Frontiers in Veterinary Science, 2021)
The bovine Escherichia coli O157:H7 is a major foodborne pathogen to cause severe bloody diarrhea, hemorrhagic colitis, and hemolytic uremic syndrome in humans. Cattle are recognized major reservoir and source of E. coli O157:H7. We investigated the antibiotic resistance, molecular profiles, and intrinsic relationship between 21 isolates of E. coli O157:H7 from cattle farms and slaughtering house in Xinjiang. Using pulsed-field gel electrophoresis (PFGE) molecular typing, 2 types of PFGE were revealed through cluster analysis, including clusters Ⅰ and Ⅱ, with 66% and 100% similarity of PFGE spectra between 21 isolates. We also detected that 18 isolates (86%) carried at least one virulence gene, 16 isolates (76%) carried the eae gene, and 7 (33%) carried the stx1+stx2+eae+hly+tccp genes. Eighteen isolates were susceptible to antibiotics. Three isolates were resistant to antibiotics, and 2 were multi-drug resistant. One of the 2 multi-drug resistant isolates detectably carried the blaCTX-M-121 gene. This is the first finding of the blaCTX-M-121 gene detected in E. coli O157:H7 isolated from cattle in Xinjiang. The blaCTX-M-121 gene is transferable between the bacterial strains via plasmid transmission. The results indicated that E. coli O157:H7 may have undergone clonal propagation in cattle population and cross-regional transmission in Xinjiang China.